Healthcare-associated infections and their relationship with insects as transmission vectors in surgical areas - Bolaño-Arenas, Jandro; Vásquez-Avendaño, Emilse; Márquez-Blanco, Norka; Amador-De Alvarino, María (Revista Colombiana de Entomología, 2023)
Healthcare-associated infections (HAIs) are adverse events. Insects, their potential vectors of microorganisms, are a risk factor for HAIs. Surgical site infections are a type of HAIs that will produce the presence of insect vectors in this area. A literature review was carried out to characterize this phenomenon in surgical areas. Eighteen published scientific papers were selected that show the detection and identification of insects as carriers of potential microorganisms that cause HAI in different hospital areas that do not include surgery. Detection and identification methods include microbiological and/or molecular methods that include non-testing of cleaning, disinfection, and sterilization solutions. Only one had carried out the three processes before the publication of potential agents in insects. There are no studies that characterize HAI in surgical areas related to the presence of insects, although there are reports of these adverse events. Therefore, it should be considered as a risk factor for the development of surgical site infections. Studies should be carried out to show the relationship between the development of an SSI such as an HAI and these vectors, in order to prevent its appearance by improving the processes of asepsis and antisepsis in surgical areas.